Psychometric study of a scale on the use of video games for the initial training of teachers - Muñoz González, Juan Manuel; Ariza Carrasco, Cristian; Hidalgo Ariza, María Dolores; Romero Esquinas, María Helena (Frontiers in Education, 2022)
The present study is focused on analyzing the properties and psychometric characteristics of the Questionnaire about the use of video games in Higher Education. Specifically, in this work we focus on the use of a classic video game, such as Lemmings, to work on the curriculum of the Early Childhood Education stage. The instrument was created ad hoc, based on a Likert scale of 5 response options and three dimensions: student / player profile, quality of the video game and assessment of the video game as a teaching resource. Regarding validity, two studies have been carried out, one with an exploratory nature with half of the sample, 131 participants; and another confirmatory with the total number of the participants, 261 students from the Early Childhood Education Degree at the University of Córdoba (Spain), considering the convergent and discriminant validity coefficients. Lastly, a correlational study was also carried out to clarify the relationships established between the different dimensions of the questionnaire. The results achieved demonstrate that the instrument obtained had a coherent and adequate internal structure with the theoretical assumptions initially raised, as the goodness-of-fit indexes of the confirmed model were high, at the same time showing high validity and reliability.